Accounting for total work in labour statistics - Andrea Brandolini; Eliana Viviano (Journal for Labour Market Research, 2016)
The interest for household production has grown since the release of the new System of National Accounts in 2008. In this paper we analyse how accounting for own-use production may affect labour statistics. Traditional headcount ratios may not be very informative when employment rates consider both home and market production, as most people are engaged in at least one of those activities. Hence, we propose a general class of indices based on the hours spent on each type of work that encompasses headcount indicators as a special case. Our empirical analysis based on time use data for a selected group of countries shows that international rankings are sensitive to the shift from headcounts to hour-weighted indices and that accounting for own-use production changes considerably the picture on the work burden of men and women.
Keywords: J22; J21; 330; Eigenarbeit; private Haushalte; Wertschöpfung; volkswirtschaftliche Gesamtrechnung; Arbeitsstatistik; Erwerbsarbeit; Hausarbeit; Arbeitszeit; Arbeitsintensität; Männer; Frauen; Zeitverwendung - internationaler Vergleich; Frankreich; Bundesrepublik Deutschland; Italien; Niederlande; Großbritannien; USA